The Palgrave Handbook of African Oral Traditions and Folklore
XLIX, 1026 p. 145 illus., 66 illus. in color.
Keywords: “This volume is not a displacement of the late 1990s/early 2000s publications on folklore in Africa, in which African functional aesthetics gave way to Western formal aesthetics, but is a definitive source book of 50 original essays which provide a multidisciplinary study of the undercurrents of African and African Diaspora folklore and oral traditions – indeed a tour de force work in the currency and originality of its ‘African voice and perspective.” – Pamela J. Olubunmi Smith, Professor Emerita, University of Nebraska at Omaha, USA “This is a comprehensive, well-researched, and impressive volume that offers significant insights and perspectives into the dynamics of oral traditions and folklore in Africa and the African Diaspora. Systematically and thematically arranged with an interdisciplinary approach, the volume is enlightening and riveting. The volume is a must-read for professionals, students, and lovers of culture.” – Julius O. Adekunle, Professor of History, Monmouth University, USA This handbook offers the most comprehensive, analytic, and multidisciplinary study of oral traditions and folklore in Africa and the African Diaspora to date. Preeminent scholars Akintunde Akinyemi and Toyin Falola assemble a team of leading and rising stars across African Studies research to retrieve and renew the scholarship of oral traditions and folklore in Africa and the Diaspora just as critical concerns about their survival are pushed to the forefront of the field. With five sections on the central themes within orality and folklore – including engagement ranging from popular culture to technology, methods to pedagogy – this handbook is an indispensable resource to scholars, students, and practitioners of oral traditions and folklore preservation alike. This definitive reference is the first to provide detailed, systematic discussion, and up-to-date analysis of African oral traditions and folklore. Akintunde Akinyemi is Professor and Chair in the Department of Languages, Literatures, and Cultures at the University of Florida, USA. Toyin Falola is the Jacob and Frances Sanger Mossiker Chair in the Humanities and a Distinguished Teaching Professor at the University of Texas at Austin, USA.